مدى ثبوت التأذين والإقامة في أذني المولود: رؤية حديثية = The authenticity level of calling Aḍhān and Iqāmah in the ears of newly born baby: a view point based on hadith science study - Gazdar, Muhammad Amir; Abul Lais, Mohammed (Kolej Universiti Islam Selangor (KUIS), 2017)
This research presents a view point regarding Prophetic traditions on the issue of calling aḍhān and iqāmah in the ears of a newly born baby. The study is aimed to probe the authenticity of this ritual. The significance of this act is vital as it is the first act which is generally practised on newly born babies by the majority of Muslims as an Islamic ritual with utmost sanctification. It is seen as an established Islamic tradition for both male and female babies upon their birth. The methodology used was extended to two phases: inductive and critical. Preliminary method revolved around the thorough scrutiny of all traditions of the Holy Prophet (s.a.w.) and narratives of his Companions on the subject. These are collected, referenced and examined by applying the method of takhrīj and studied according to the pattern of hadīh studies. The second phase involved the evaluation of available traditions and critical appreciation of their chain (sanad) and text (matan) according to the science of hadīh. It is made by issuing the final verdict on their authenticity in keeping with the rules of verification of hadīh. The researcher reached the conclusion that nothing is proved and authentic in all the Prophetic narratives on calling aḍhān and iqāmah in the ears of a newly born baby. Therefore, according to the absolute and research based opinion; we are not able to use them to prove its legitimacy in Islam.